# Chemistry

X2 + Y2 <=> 2XY

0.50 mole each of X2 and Y2 are placed in a 1.0 litre vessel and allowed to reach equilibrium at a given temperature. The equilibrium concentrations of XY is found to be 0.025 mol/L. What is the equilibrium cosntant for this reaction?

Do I just get the concentration of X2 and Y2 by dividing 0.5 mol with 1L and then take the answer and the equilibrium concentrations of XY - 0.025 mol/l and divide 0.025 by the concentration of X2 and Y2 in order to get the equilibrium constant?

Your explanation isn't clear to me but it sounds like you have it ok.
initial concentrations:
X2 = 0.5 M
Y2 = 0.5 M
XY = 0

change:
XY = +0.025
X2 = 0.025-(1mol X2/2 mol XY)=1/2*0.025
Y2 = 0.025-(1mol Y2/2 mol XY)=1/2*0.025

eqilibrium:
XY = 0.025
X2 = 0.5 - 1/2(0.025)
Y2 = 0.5 - 1/2(0.025)

Keq = (XY)^2/(X2)(Y2)=
(0.025)^2/(0.4875)^2 = ??

Check my thinking. Check my arithmetic.

1. 👍 0
2. 👎 0
3. 👁 128

## Similar Questions

1. ### pre-cal

Use Pascal's triangle to expand the expression. (x − y)5 so I tried to work this out: (x-y)^5 = [(x-y)(x-y)][(x-y)(x-y)](x-y) (x-y)^2 = (x-y)(x-y) = x^2 - 2xy + y^2 x^2 - 2xy + y^2)(x^2 - 2xy + y^2) = x^4 -4x^3y + 6x^2y^2 -

asked by James on August 12, 2015
2. ### Algebra

Simplify (2xy^2+3)((2xy^2)^2-(2xy^2)(3)+(3)^2) This reminds me of (U+a)(U^2- aU + a^2). When mulipltiplied out, one gets a cubic equation. Do you remember the formula for factoring the sum of two cubes? a^3+b^3= ????

asked by Juri on August 9, 2007
3. ### Algebra

I thought number 4 on this list was incorrect but didn't know how to fully explain it here is the list that I have. Please look at the following simplification of an algebraic expression. Which line contains the mistake and why?

asked by Linda on March 8, 2013
4. ### Math

Can 2xy - y - 1 be factored out? How? about all you can do is take the common y out of the first two terms; that in itself is not much help. dont know if this is rite or not..but just a guess.. assuming 2xy - y - 1 = 0 2xy - y = 1

asked by Sarah on August 15, 2007
5. ### Algebra

Please look at the following simplification of an algebraic expression. Which line contains the mistake and why? Line 1: (2x + 6x) + 4y + 3x - 2xy Line 2: (8x) + 4y + 3x - 2xy Line 3: 8x + 3x + 4y - 2xy Line 4: 11x + 4y - 2xy Line

asked by Linda on March 11, 2013
6. ### Algebra (new one since I put "match" (bad speller)

I have a few match problems that I can't figure out. 1.solve: 3x+5=x√7 (that's a radical sign) 2.factor: (2k+3)2-(2x+3)(y-2)-20(y-2)2 (the "2" after (2k+3) ans (y-2) is suppose to be a square sign. thanks if you can help, or

asked by Sarah on January 21, 2007

which will become a buffer in 1L of H2O? a) 0.3 mole KOH & 0.3 mole HBr b) 0.5 mole NH3 & 0.5 mole HCl c) 0.2 mole NaCl & 0.3 mole HCl d) 0.2 mole NaOH & 0.2 mole HBr e) 0.4 mole HC2H3O2 & 0.2 mole NaOH I think that the answer is

asked by Zac on April 29, 2012
8. ### Chemistry

Determine the simplest formula for compounds that have the following analyses. The data may not be exact. A. 28.5% iron, 48.6% O, 22.9% S This is what I did: 28.5g Fe 1 mole Fe/55.847g = .51 mole 48.6g O 1 mole O/15.999g = 3.04

asked by Chopsticks on January 21, 2009
9. ### Calculus

Consider the equation: x^2 - 2xy + 4y^2 = 64 Write an expression of the slope of the curve at any point. (y^p)= y prime My work 2x - 2(xy^p + y) + 8yy^p = 0 2x -2xy^p - 2y + 8yy^p = 0 -2xy^p + 8yy^p = 2y -2x factored out y^p and

asked by Anonymous on October 29, 2008
10. ### Calculus

Find y" by implicit differentiation. x^3+y^3 = 1 (x^3)'+(y^3)' = (1)' 3x^2+3y^2(y') = 0 3y^2(y') = -3x^2 y' = -3x^2/3y^2 y' = -x^2/y^2 y" = [(y^2)(-x^2)'-(-x^2)(y^2)']/y^4 y" = [(y^2)(-2x)-(-x^2)(2y)]/y^4 y" =

asked by Justin on September 27, 2015
11. ### algebra need help

how would you solve something like this 2xy X 3y X -y ______________ 2xy X 3xy X x The X are multiplication MY answer is -y over x2y the 2 goes above the x

asked by jennifer on September 14, 2016

More Similar Questions